2011
DOI: 10.1038/emboj.2010.349
|View full text |Cite
|
Sign up to set email alerts
|

The ZEB1/miR-200 feedback loop controls Notch signalling in cancer cells

Abstract: Notch signalling is important for development and tissue homeostasis and activated in many human cancers. Nevertheless, mutations in Notch pathway components are rare in solid tumours. ZEB1 is an activator of an epithelial–mesenchymal transition (EMT) and has crucial roles in tumour progression towards metastasis. ZEB1 and miR‐200 family members repress expression of each other in a reciprocal feedback loop. Since miR‐200 members target stem cell factors, ZEB1 indirectly induces stemness maintenance and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
278
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(295 citation statements)
references
References 33 publications
9
278
1
2
Order By: Relevance
“…34 Significantly, relevant molecular targets of the miR-200/ZEB1 loop include the stem cell-associated factors BMI1, SOX2, KLF4, 14 and Notch signaling pathway. 35 Summarizing, we demonstrated for the first time that absence or severe dowregulation of E-cadherin associated with ZEB1 overexpression is characteristic of undifferentiated endometrial carcinomas. As these alterations are very infrequently seen in grade 3 endometrioid endometrial carcinomas and can be evaluated by immunohistochemistry, our results have important implications for the differential diagnosis of both types of tumors, which show different prognosis.…”
Section: Discussionmentioning
confidence: 57%
“…34 Significantly, relevant molecular targets of the miR-200/ZEB1 loop include the stem cell-associated factors BMI1, SOX2, KLF4, 14 and Notch signaling pathway. 35 Summarizing, we demonstrated for the first time that absence or severe dowregulation of E-cadherin associated with ZEB1 overexpression is characteristic of undifferentiated endometrial carcinomas. As these alterations are very infrequently seen in grade 3 endometrioid endometrial carcinomas and can be evaluated by immunohistochemistry, our results have important implications for the differential diagnosis of both types of tumors, which show different prognosis.…”
Section: Discussionmentioning
confidence: 57%
“…In one of the earliest studies of pancreatic and colon cancers, Wellner et al discovered that Zeb1 promotes tumorigenicity by repressing stemness-inhibiting miRNAs [156]. In follow up investigations, they determined that the miR-200 family targets Notch pathway components, such as Jagged1, to mediate enhanced Notch activation of Zeb1 in two aggressive types of human solid tumors [157]. MiR-200 essentially counteracts classical EMT properties such as cell motility, and suppresses translation of stem cells factors, including Bmi1.…”
Section: Inflammation-inducible Emt Drives Stemness and Contributes Tmentioning
confidence: 99%
“…Depletion of Zeb1 and Zeb2 decreases the proportion of CSCs in the population of transformed ER-Src cells (11), and Zeb1 and Zeb2 repress the expression of miR-200 family members (24). As the miRNAs involved in CSC function are coordinately down-regulated in CSC cells, we examined whether Zeb1 and Zeb2 affect the expression of the CSC-regulating miRNAs (Fig.…”
Section: Zeb1 and Zeb2 Inhibit Expression Of Multiple Mirnas Involvedmentioning
confidence: 99%
“…In addition, miR-200 affects CSC function by directly targeting Bmi1 (9,20) and Suz12 (11), which, respectively, are components of the PRC1 and PRC2 polycomb complexes that repress transcription. Targets of miR-200 also include proteins involved in secretion (21), cell motility, and anoikis resistance (22), SIRT1 (23), and the Notch pathway (24), and it has been suggested that the stem cell factor Klf4 is also a target (20).…”
mentioning
confidence: 99%